From Molecular Mechanisms to Therapeutics: Understanding MicroRNA-21 in Cancer - Jiho Rhim; Woosun Baek; Yoona Seo; Jong Heon Kim (Cells, 2022)
MicroRNAs (miRNAs) are small noncoding RNAs that play an important role in regulating gene expression at a posttranscriptional level. As one of the first discovered oncogenic miRNAs, microRNA-21 (miR-21) has been highlighted for its critical role in cancers, such as glioblastoma, pancreatic adenocarcinoma, non-small cell lung cancer, and many others. MiR-21 targets many vital components in a wide range of cancers and acts on various cellular processes ranging from cancer stemness to cell death. Expression of miR-21 is elevated within cancer tissues and circulating miR-21 is readily detectable in biofluids, making it valuable as a cancer biomarker with significant potential for use in diagnosis and prognosis. Advances in RNA-based therapeutics have revealed additional avenues by which miR-21 can be utilized as a promising target in cancer. The purpose of this review is to outline the roles of miR-21 as a key modulator in various cancers and its potential as a therapeutic target.